2021
DOI: 10.3390/ijms221810094
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-499 Polymorphism and Its Regulatory Networks with Hashimoto Thyroiditis Susceptibility: A Population-Based Case-Control Study

Abstract: Hashimoto thyroiditis (HT) is a common autoimmune disorder with a strong genetic background. Several genetic factors have been suggested, yet numerous genetic contributors remain to be fully understood in HT pathogenesis. MicroRNAs (miRs) are gene expression regulators critically involved in biological processes, of which polymorphisms can alter their function, leading to pathologic conditions, including autoimmune diseases. We examined whether miR-499 rs3746444 polymorphism is associated with susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 104 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…Emerging evidence suggests that single-nucleotide polymorphisms (SNPs) in immunoregulatory genes may functionally impede the normal development of central and peripheral tolerance and alter the interaction of T cells with antigen-presenting cells (APCs) in the immune synapse. Numerous studies have found that gene polymorphisms, such as CTLA4 ( 93 95 ), TNF -308 ( 96 ), TRAF1 ( 97 ), microRNA ( 98 ), NFKB1 ( 99 ), NLRP1 ( 100 ), ICAM-1 ( 101 ), ZFAT ( 102 ) and so on, are significantly associated with AITD. Racial variations in AITD prevalence further accentuate potential genetic polymorphisms and the role of genetic susceptibility in the etiology of AIT ( 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that single-nucleotide polymorphisms (SNPs) in immunoregulatory genes may functionally impede the normal development of central and peripheral tolerance and alter the interaction of T cells with antigen-presenting cells (APCs) in the immune synapse. Numerous studies have found that gene polymorphisms, such as CTLA4 ( 93 95 ), TNF -308 ( 96 ), TRAF1 ( 97 ), microRNA ( 98 ), NFKB1 ( 99 ), NLRP1 ( 100 ), ICAM-1 ( 101 ), ZFAT ( 102 ) and so on, are significantly associated with AITD. Racial variations in AITD prevalence further accentuate potential genetic polymorphisms and the role of genetic susceptibility in the etiology of AIT ( 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…About 49% of patients with hypothyroidism have an autoimmune-related etiology ( 7 ). Hashimoto thyroiditis (HT), a chronic autoimmune thyroid disease, is the main cause of hypothyroidism ( 8 ) and has a strong genetic background ( 9 ). These suggested that genetic factors play an important role in the development of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs broadly regulate physiological and pathological processes in humans, including the process of AS, and may potentially affect the susceptibility to IS through SNPs. Previous evidence suggested that rs2910164, rs2292832, rs11614913, and rs3746444 affected the function of miRNAs, [5][6][7][8][9][10][11] which were shown to be involved in the processes of AS, such as inflammation, [12][13][14][15] endothelial injury, [16][17][18][19] lipid metabolism, [9][10][11] immune response, [19] and angiogenesis. [20][21][22][23][24][25] In addition, miR-146a-3p and miR-149-5p was shown to be involved in the regulation of AS plaque This study was supported by grants from the National Natural Science Foundation of China (81473763), and was supported by grants from the Science Foundation of Heilongjiang University of Chinese Medicine (2017sit01 and2019BS08).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs broadly regulate physiological and pathological processes in humans, including the process of AS, and may potentially affect the susceptibility to IS through SNPs. Previous evidence suggested that rs2910164, rs2292832, rs11614913, and rs3746444 affected the function of miRNAs, [5–11] which were shown to be involved in the processes of AS, such as inflammation, [12–15] endothelial injury, [16–19] lipid metabolism, [9–11] immune response, [19] and angiogenesis. [20–25] In addition, miR-146a-3p and miR-149-5p was shown to be involved in the regulation of AS plaque stability.…”
Section: Introductionmentioning
confidence: 99%